2022
DOI: 10.3390/f13081253
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Analyses of the 4-Coumarate: CoA Ligase (4CL) Gene Family in Eucommia ulmoides

Abstract: 4-Coumarate: coenzyme A ligase (4CL) is an important rate-limiting enzyme in phenylpropanoid metabolism that plays an important role in the biosynthesis of phenylpropanoid, flavonoid, lignin and other secondary metabolites in plants. However, the family members and functions have not been identified in Eucommia ulmoides (E. ulmoides). In this study, 35 Eu4CLs were identified in the E. ulmoides genome, and the gene structure, conserved domain, evolutionary relationship and expression pattern were comprehensivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…We identified a total of 36 and 31 4CL gene members in J. regia and J. mandshurica, respectively. The large variation in the number of 4CL genes in different species [35][36][37][38][39] may be related to the gene duplication events experienced by different species during evolution. WGD is the most common gene duplication pattern, and WGD events may enhance the adaptability of species to their environment [77].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified a total of 36 and 31 4CL gene members in J. regia and J. mandshurica, respectively. The large variation in the number of 4CL genes in different species [35][36][37][38][39] may be related to the gene duplication events experienced by different species during evolution. WGD is the most common gene duplication pattern, and WGD events may enhance the adaptability of species to their environment [77].…”
Section: Discussionmentioning
confidence: 99%
“…The same phenomenons were observed in most species of 4CL gene families. For example, the number of exons in Md4CL [39] and Eu4CL gene families [37] also ranged from 1 to 23. An increment in the number of introns in genes may be better than harm to the plant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the St4CL5 subcellular localization assay was performed. The 4CL proteins are predominantly distributed in bio-membrane system of plant cell [ 59 ], but Peucedanum praeruptorum Dunn Pp4CL1 and Pp4CL10, which have different functions compared to other Pp4CL family genes, are localized to the cytosol [ 60 ]. Recent results of subcellular localization of Cs4CL1 and Cs4CL2 in Camellia sinensis have shown that Cs4CL1 and Cs4CL2 were also mainly distributed in the cytosol [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, promoter sequences of the potato 4CL gene family members all contain photoresponsive elements. UV stress can promote the up-regulation of St4CL6 and St4CL8 but inhibit the expression of St4CL5 ( Zhong et al., 2022 ). Studies in tea tree also showed that the promoters of two 4CL genes, Cs4CL1 and Cs4CL2 , contained 9 kinds of light response elements, and Cs4CL2 was induced by UV-B ( Li et al., 2022b ).…”
Section: Discussionmentioning
confidence: 99%